1994
DOI: 10.1111/j.1365-3083.1994.tb03349.x
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction via MHC Class‐I Molecules in T cells

Abstract: SUMMARY The data reviewed in this paper, suggest that besides their role in presentation of antigenic pcptides to T cells, MHC‐I molecules may play an important role in the fine‐tuning of signal transmission across the cell membrane by their associations with a variety of cell‐surface receptors regulating cell growth and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
(9 reference statements)
2
34
0
Order By: Relevance
“…Several reports have demonstrated that activation induced by cross-linking of HLA class I molecules depends on an association between these molecules and other cell surface proteins such as interleukin-2R or CD3/TCR (45). We further observed that inhibition of cytoskeleton rearrangement by cytochalasin B or D, which may inhibit association of cell surface molecules, prevents HLA class I-but not Fas-mediated apoptosis.…”
Section: Discussionsupporting
confidence: 63%
“…Several reports have demonstrated that activation induced by cross-linking of HLA class I molecules depends on an association between these molecules and other cell surface proteins such as interleukin-2R or CD3/TCR (45). We further observed that inhibition of cytoskeleton rearrangement by cytochalasin B or D, which may inhibit association of cell surface molecules, prevents HLA class I-but not Fas-mediated apoptosis.…”
Section: Discussionsupporting
confidence: 63%
“…Cross-linking of MHC I molecules triggers early (rises in free Ca ϩϩ , tyrosine phosphorylation) and late (cytokine production, increased receptor display, and cell proliferation) responses by T-cells (Tscherning and Claësson, 1994;Bregenholt et al, 1996). The effects of cross-linking may require one or more signaling cascades that involve phosphorylation on the conserved cytoplasmic tyrosine of HLA.…”
Section: Discussionmentioning
confidence: 99%
“…Although MHC class I molecules expressed by other cell types such as macrophages, mast cells, fibroblasts, and ECs have been shown to transduce proliferative signals, the intracellular signaling pathways remain to be elucidated (38).…”
mentioning
confidence: 99%